Whole Pancreas and Islet Cell Transplantation for Patients with Type 1 Diabetes Mellitus: A Mini-Review and Middle East–North Africa Experience - Samih Abed Odhaib; Adel G. Mohammed; Hinde Iraqi (Journal of Diabetology)
Pancreas and islet cell transplantations (ICT) have significantly advanced the management of type 1 diabetes mellitus, offering viable alternatives for patients with severe glycemic instability or end-stage renal disease. Pancreas transplantation, particularly in the form of simultaneous pancreas–kidney transplantation, provides sustained glycemic control, reduces diabetes-related complications, and enhances quality of life. ICT, a less invasive alternative, effectively stabilizes blood glucose levels and minimizes hypoglycemic episodes but offers lower insulin independence rates. In the Middle East and North Africa (MENA) region, pancreas and islet transplantation programs have been gradually evolving, with notable progress in countries such as Iran and Saudi Arabia. However, challenges such as limited donor availability, technical complexities, and cultural barriers hinder their widespread implementation. The need for public awareness, healthcare infrastructure development, and international collaborations is critical for scaling these life-changing therapies across the region. This review examines the indications, modalities, and outcomes of pancreas and ICT globally, with a particular focus on the progress and challenges within the MENA region. It highlights advancements in surgical techniques, immunosuppressive regimens, and donor organ preservation that have improved transplantation outcomes over time. Furthermore, the review underscores the importance of implementation of tailored strategies to overcome regional barriers and expand access to these transformative therapies, offering valuable insights into the future directions of diabetes management through transplantation.